“I had post-concert depression”: A study of Lucy fans after the Jakarta concert - Ramadhiansyah, Dimas (Jurnal Komunikasi, 2025)
This study examines the impact of Hallyu, particularly K-pop, on fan communities in Indonesia, focusing on the phenomenon of Post-Concert Depression (PCD) often experienced by fans after major concerts. Using the netnography method, the study observes the interaction dynamics within a WhatsApp group of LUCY fans following the "We Are Landing in Jakarta" concert in January 2024. Findings show that social support within online communities helps alleviate PCD by sharing concert memories, photos, and emotional reflections. The group’s activities evolved from concert discussions to other topics like artist news and fan events, creating a dynamic communication space. Over time, relationships within the group became more personal, transforming it into a digital family grounded in empathy. Digital communities like "Kepulauan LUCY" demonstrate the potential to build strong emotional bonds online.